2006
DOI: 10.4049/jimmunol.176.1.372
|View full text |Cite
|
Sign up to set email alerts
|

Nitration and Inactivation of IDO by Peroxynitrite

Abstract: IDO induction can deplete l-tryptophan in target cells, an effect partially responsible for the antimicrobial activities and antiallogeneic T cell responses of IFN-γ in human macrophages, dendritic cells, and bone marrow cells. l-Tryptophan depletion and NO production are both known to have an antimicrobial effect in macrophages, and the interaction of these two mechanisms is unclear. In this study we found that IDO activity was inhibited by the peroxynitrite generator, 3-(4-morpholinyl)sydnonimine, in PMA-dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 45 publications
4
55
2
Order By: Relevance
“…4D). Previous studies have shown that protein nitration can have an inhibitory effect on enzymatic activity (21). To test whether the decrease in TCoB phosphorylation in NO donor-treated cells was not caused by nitration of Pak1 itself, we tested the nitration status of Pak1.…”
Section: Nitration Antagonizes Signaling-dependent Phosphorylation Ofmentioning
confidence: 99%
“…4D). Previous studies have shown that protein nitration can have an inhibitory effect on enzymatic activity (21). To test whether the decrease in TCoB phosphorylation in NO donor-treated cells was not caused by nitration of Pak1 itself, we tested the nitration status of Pak1.…”
Section: Nitration Antagonizes Signaling-dependent Phosphorylation Ofmentioning
confidence: 99%
“…The mechanisms involved in post-transcriptional and post-translational regulation of IDO1 enzyme activity remain elusive but may involve nitration of the enzyme by peroxynitrite [34].…”
Section: Discussionmentioning
confidence: 99%
“…In several cell systems, IDO expression and activity have been shown to be inhibited by NO. For example, NO enhances proteosomal degradation of IDO, and NO donors inactivate IDO by inducing nitration of critical tyrosine residues (25,33). Therefore, we investigated the relationship between IDO and iNOS expression in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…IDO biosynthesis is regulated at several steps. In particular, IDO expression and/or activity have been shown to be downregulated by NO in several cell culture and cell-free systems (25,33,52). We therefore asked whether NO generated by astrocyte iNOS can affect IDO expression or activity.…”
mentioning
confidence: 99%